'Bidding up' the national cause: Józef Piłsudski and the Central Powers' Kingdom of Poland. Issue 1 (2nd January 2020) - Schwonek, Matthew R.
ABSTRACT: On 5 November 1916 a proclamation in the name of Emperor Wilhelm II and Emperor-King Francis Joseph I called to life the Kingdom of Poland and Polish Armed Forces, while a Provisional State Council was summoned soon afterwards. On the council, Brigadier General Józef Piłsudski of the Polish Legions mounted an effort to engage the Central Powers and breathe life into the project. Unwilling to settle for building the elements of statehood, Piłsudski sought nothing less than a government and an army with real power. From the outset Piłsudski dangled the Legions, a military contribution, as the object of negotiation, in a process he called ' licytacja' or 'bidding up'. Taking the offensive granted control of the agenda and enhanced his power. This strategy involved political work as well as building military organs. Above all, it meant driving the state council, using pressure from within and without, to press for concessions and withhold cooperation until the former materialized. Although the Legions were moved to the kingdom, German and Habsburg officials deflected requests for national control. German intransigence as well as the US entry into the war and revolution in Russian led Piłsudski to adopt progressively more radical positions. He came to favour a dramatic gesture, putting at risk the kingdom. In July 1917 he engineered a demonstration by the soldiery, rejecting an oath of loyalty. This put paid to the idea of a government and army, while it put Piłsudski behind bars. Analysis reveals the dynamics between great powers and their clients. While the former held all the cards, the latter could not conform to the role of supplicants. Piłsudski's strategy of withholding cooperation, saying 'no', conferred a measure of power vis-à-vis the Central Powers. This power was necessarily fleeting and, in the end, had only the capability of sabotaging collaboration. The case sheds light on political conditions and national action in the period, during which imperial regimes began to crumble, but a new order had yet to take shape.